New combinations in the Neotropical genus Miconia (Melastomataceae: Miconieae) - Gamba, Diana; Almeda, Frank (Phytotaxa, 2018)
In our published monograph of the Octopleura clade of Miconia (Ruiz & Pavón 1794: 60), we proposed a number of new combinations and new names to reflect the nested position of this group of 33 species within the large and megadiverse neotropical genus Miconia based on morphological and molecular data sets (Gamba & Almeda 2014). At least three of the species names we proposed or accepted in that monograph present nomenclatural problems in need of correction. The name Miconia magnifolia Gamba & Almeda (2014: 91), which was illegitimate and nomenclaturally superfluous, has been rejected and replaced with Miconia solearis (Naudin 1851: 339) Gamba & Almeda (2015: 199). Two other names, Miconia spiciformis Gamba & Almeda (2014: 130) and Miconia neomicrantha Judd & Skean (1991: 62) must also be rejected and replaced. The former is superfluous and illegitimate and our acceptance of the latter species overlooked the epithet of a heterotypic synonym that was available and should have been adopted for a new combination. We here replace these latter two names with the following combinations and provide a summary of relevant synonymy.